2018
DOI: 10.1007/s00425-018-2977-8
|View full text |Cite
|
Sign up to set email alerts
|

AgMYB2 transcription factor is involved in the regulation of anthocyanin biosynthesis in purple celery (Apium graveolens L.)

Abstract: This study showed that an R2R3-MYB transcription factor, AgMYB2, functions in anthocyanin biosynthesis and accumulation in purple celery. Anthocyanins are involved in tissue coloration and stress response in plants. Foods containing high anthocyanin content are also beneficial to human health. Purple celery accumulated amounts of anthocyanins in the petioles. The biosynthesis of anthocyanin in plants is mainly regulated by the R2R3-MYB transcription factor (TF). However, the R2R3-MYB TF that controls anthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Moreover, the transcript levels of several key structural genes exhibited significant increases in both RsPAP2-overexpressing Arabidopsis plants and radish cotyledons. This phenomenon has also been noted for genes in other plants, such as OvPAP2 in oilseed rape 42 , NtMYB2 in Chinese narcissus 43 , and AgMYB2 in purple celery 44 . These findings indicated that RsPAP2 might promote ATC biosynthesis by positively regulating several critical ATC-related genes in radish.…”
Section: Rspap2 Either Alone or With Rstt8 Regulates Atc Accumulatisupporting
confidence: 56%
“…Moreover, the transcript levels of several key structural genes exhibited significant increases in both RsPAP2-overexpressing Arabidopsis plants and radish cotyledons. This phenomenon has also been noted for genes in other plants, such as OvPAP2 in oilseed rape 42 , NtMYB2 in Chinese narcissus 43 , and AgMYB2 in purple celery 44 . These findings indicated that RsPAP2 might promote ATC biosynthesis by positively regulating several critical ATC-related genes in radish.…”
Section: Rspap2 Either Alone or With Rstt8 Regulates Atc Accumulatisupporting
confidence: 56%
“…An R2R3-MYB TF, OjMYB1, was reported to be involved in anthocyanin biosynthesis in Oenanthe javanica [ 5 ]. AgMYB2 is involved in the regulation of anthocyanin biosynthesis in purple celery [ 21 ]. MdMYBA induces anthocyanin accumulation in the reproductive tissues of transgenic tobacco [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The total number of NBS-LRR genes was 146 in carrot 20 , 176 in Arabidopsis 57 , 107 in maize 58 , and 472 in rice 59 . Among these genes in the celery genome, one class, NBS, presented a markedly greater number in celery (126 genes) than in other plants including carrot (19), Arabidopsis (1), maize (7) and rice (25). The NBS-LRR genes present in monocotyledons and dicotyledons showed different characteristics.…”
Section: Celery-specific Transcription Factors and Disease Resistancementioning
confidence: 99%
“…In particular, the content of apigenin in celery is higher than that in other plants 6 . Many studies on the isolation, identification, and application of flavonoids in celery have been carried out 4,7,8 . Apigenin and luteolin exhibit a wide range of pharmacological effects, including anti-bacterial, anti-oxidation, and cardiovascular protective effects 9,10 .…”
Section: Introductionmentioning
confidence: 99%